2013
DOI: 10.3389/fpubh.2013.00064
|View full text |Cite
|
Sign up to set email alerts
|

Local Health Department Epidemiologic Capacity: A Stratified Cross-Sectional Assessment Describing the Quantity, Education, Training, and Perceived Competencies of Epidemiologic Staff

Abstract: Introduction: Local health departments (LHDs) must have sufficient numbers of staff functioning in an epidemiologic role with proper education, training, and skills to protect the health of communities they serve. This pilot study was designed to describe the composition, training, and competency level of LHD staff and examine the hypothesis that potential disparities exist between LHDs serving different sized populations.Materials and Methods: Cross-sectional surveys were conducted with directors and epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Further study on the impact factors using stepwise regression analysis is presented in Table 5 . The results show five relevant factors of the PHWs’ self-evaluation competency scores: economic level, age, years of working (yeas as a PHW), major, and title [ 49 ]. As previously mentioned, a higher economic level causes higher competency scores.…”
Section: Discussionmentioning
confidence: 99%
“…Further study on the impact factors using stepwise regression analysis is presented in Table 5 . The results show five relevant factors of the PHWs’ self-evaluation competency scores: economic level, age, years of working (yeas as a PHW), major, and title [ 49 ]. As previously mentioned, a higher economic level causes higher competency scores.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study extended the work of previous CSTE studies and described the composition, training, and competency level of LHD staff functioning in an epidemiologic role within their organization. 24 However, previous ECA surveys have not described how the epidemiology capacity within an LHD is used during routine vs. emergency situations, where the roles and responsibilities may shift due to staff availability, competence, and response needs. Understanding the role of nontraditional sources of epidemiologic support and ensuring that these sources are adequately trained and have the resources to meet the epidemiologic needs is essential to an effective public health response during infectious disease emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments by national organizations such as the Association of Public Health Laboratories (APHL), Association of State and Territorial Health Officials (ASTHO), Council of State and Territorial Epidemiologists (CSTE), and National Association of County and City Health Officials (NACCHO) have shown that there are approximately 8,000 epidemiology positions in governmental public health across the U.S., which represents only 3% of the entire public health workforce [7]. In addition, little is known about the epidemiology-specific education and training of the current public health workforce [8]. In many public health agencies, epidemiology functions including disease surveillance, study design, data collection and analysis, and designing disease control methods are carried out by public health nurses or environmental health specialists [9].…”
Section: Introductionmentioning
confidence: 99%
“…In many public health agencies, epidemiology functions including disease surveillance, study design, data collection and analysis, and designing disease control methods are carried out by public health nurses or environmental health specialists [9]. One-third of epidemiology staff in small and medium jurisdictions lack formal academic training in epidemiology, limiting the overall epidemiologic capacity of the public health system [8,9].…”
Section: Introductionmentioning
confidence: 99%